Prevalence and laboratorial determinants of the clinical relevance of antibodies of undetermined specificity. Issue 6 (10th June 2019) - de Albuquerque da Veiga Conrado, Marina Cavalcanti; Cardoso, Regina A.; Dezan, Marcia Regina; Oliveira, Valeria Brito; Neto, Abel da Costa; Ziza, Karen Chinoca; Krieger, José Eduardo; Pereira, Alexandre Costa; Sabino, Ester Cerdeira; Rocha, Vanderson; Mendrone‐Júnior, Alfredo; Dinardo, Carla Luana
Abstract : Background and Objectives: Antibodies of unknown specificity (AUS) are frequently identified in the pre‐transfusion testing. These antibodies can be insignificant or potentially cause post‐transfusion haemolysis. Information about the prevalence of clinically relevant AUS is still lacking. Our aim was to predict the potential clinical relevance of AUS using the monocyte monolayer assay (MMA) and to identify the clinical and laboratorial determinants of AUS' significance. Materials and Methods: Antibodies of unknown specificity identified at a single institution from 2015–2017 were evaluated through MMA. A monocyte index (MI) of more than 5% was predictive of potential post‐transfusion haemolysis. Results: Thirty‐two patients with AUS were included in the study. Of the studied AUS, 37·5% (12/32) presented with a monocyte index (MI) more than 5%. In the group of significant AUS, 41·7% of the patients presented with sickle cell disease (SCD) and the AUS were associated with Rh antibodies in 75% of the cases. In the group of insignificant AUS, only 10% of the patients had SCD and the association with Rh antibodies was detected in 20% of the cases. The presence of Rh antibodies was independently associated with the AUS clinical relevance ( P  =   0·012). Conclusion: More than one‐third of the AUS are potentially clinically relevant, and the association with Rh antibodies is predictive of AUS relevance. Services must honour AUS in the pre‐transfusion process in order to ensure transfusion safety.